THE USE OF ARTIFICIAL INTELLIGENCE IN DIGITAL HISTORICAL INTERACTIVE PROJECTS - Скакун, Данііл; Сапицька, Олена (SWorldJournal, 2024)
The paper highlights the processes of integrating artificial intelligence into historical research by synthesizing methods of historical science, information technology and digital humanities. It is determined that AI technologies are radically changing r